Antimicrobial Resistance and Diagnostic Imaging in Infants Younger Than 2 Months Old Hospitalized With a First Febrile Urinary Tract Infection: A Population-based Comparative Study. Issue 8 (August 2016) - Hsu, Chih-Chuan; Tsai, Jeng-Dau; Ku, Min-Sho; Chen, Shan-Ming; Liao, Pei-Fen; Hung, Tung-Wei; Tsai, Min-Ling; Sheu, Ji-Nan
Abstract : Background: Data on urinary tract infection (UTI) in infants ⩽2 months of age are limited. We examined clinical characteristics, antimicrobial resistance, imaging findings and clinical outcomes in infants ⩽2 months of age and children 2–24 months of age hospitalized with the first febrile UTI. Methods: Children ⩽24 months of age hospitalized with their first-diagnosed febrile UTI were prospectively studied. Renal ultrasonography, 99m Tc-dimercaptosuccinic acid scanning and voiding cystourethrography were performed in all children. Results: Of the 388 children analyzed (255 boys and 133 girls), 61 patients were ⩽2 months of age, representing 15.7% of the whole population, whereas 327 patients were 2–24 months of age. Escherichia coli was the predominant bacterium, with similar antimicrobial resistance in the 2 groups, and associated E. coli bacteremia occurred in 9 patients (2.3%). Renal ultrasonography showed abnormal findings in 130 patients (33.5%), but there was no difference in the rate of abnormal findings between the groups. Vesicoureteral reflux (VUR) was present in 130 children (33.5%), including 93 (24%) with grades III–V VUR. VUR was more prevalent in the infants ⩽2 months of age ( P = 0.007), but there was no difference in the prevalence of grades III–V VUR between the groups. The incidence of renal scarring was 28.6% (111/388), and it did not differ between the groups. Conclusions: There are similarities in clinical characteristics, antimicrobial resistance, imaging findings and clinical outcomes after a first UTI between the young infants ⩽2 months and children 2–24 months of age. The same guidelines for the diagnosis and management after the first febrile UTI can be applied to children who are ⩽24 months of age.